2022
DOI: 10.7759/cureus.26670
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hydatid Cyst in Children: A Single-Institution Experience

Abstract: Objective: Hydatid cysts can occur in any place such as the liver, lung, spleen, kidney, brain, and soft tissue. Pulmonary hydatid cysts are more prone to rupture than liver hydatid cysts. In this study, we aimed to present the demographic characteristics, clinical symptoms, radiological findings, surgical findings, type of surgery performed, and postoperative complications of patients with pulmonary hydatid cysts.Materials and method: The files of 94 patients who were operated on for pulmonary hydatid cysts i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In certain cases, pharmacological treatment alone may be proposed. 2,5 In conclusion, this case underscores the need for a multidisciplinary approach involving surgery and pharmacological treatment in the management of pediatric pulmonary CE.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…In certain cases, pharmacological treatment alone may be proposed. 2,5 In conclusion, this case underscores the need for a multidisciplinary approach involving surgery and pharmacological treatment in the management of pediatric pulmonary CE.…”
mentioning
confidence: 72%
“…The lungs are the second most prevalent site of hydatid disease, following the liver. 2 Multiple protoscolex develop on the cyst inner surface. Protoscolex, which measures about 120 µm, contains invaginated scolex bearing suckers and hooks of the future adult cestode.…”
mentioning
confidence: 99%
“…Other studies demonstrated that the lung, rather than the liver, is the most common location for hydatid cysts in children [12,14,47]. Vascularization, negative pressure, and elasticity of the tissue seem to favor the development of cysts in the lung [13,14,61]. Another reason for the higher number of pulmonary cases could be the earlier and louder symptoms of lung cysts observed in children (e.g., cough, chest discomfort), which sometimes push parents to seek medical treatment more quickly [8].…”
Section: Discussionmentioning
confidence: 97%
“…Usually, cysts develop in the liver (70%) and lungs (20%), yet they can also be found in other organs like the brain, bones, heart, urinary, and genital tract [10,11]. However, in children, lungs are apparently more frequently affected because of the negative pressure, vascularization, and compressibility [12][13][14]. Symptomatology in the early stages of the disease is absent or mild [5].…”
Section: Introductionmentioning
confidence: 99%
“…Attention should be paid to the fact that the rate of bronchial rupture varied between 21.1 % and 53.1 % [16]. At work [17] result of surgery in 94 children with PHC was carried out. The rupture was detected in 52.5 % of patients with a diameter of HC of <10 cm.…”
Section: оригинальные исследованияmentioning
confidence: 99%